KUALIFIKASI SUMBER DAYA MANUSIA DI LEMBAGA KEUANGAN SYARIâAH - ., Muhammad (Al-Mawarid Jurnal Hukum Islam, 2003)
Shariâah Finance Institution has developed progressively nowadays, for instance Shariâah Banking, Shariâah Insurance, Shariâah Exchange,Shariâah Pawning, and Baitul Mal wat-Tamwil. For that reason, the existence of Shariâah Finance Institution demands investor and manager those have certainly criteria. The minimum criteria that should be owned by finance institution either from the institution, investor or manager are the credibility and the professionalility. The credibility and professionality become so important because of (1) in order Shariâah Finance Institution has a competitive advantage, and (2) problem of human resources that indicates the lower professionalities, lower understanding regarding moral and Islamic business ethics , and (3) to increase the professionalities is not only including the skill but also including a moral commitment and business ethic that originated from religion (Islam) as a guidance how to conduct Shariâah Finance Institution in the future.